An Analysis of Competitiveness and Government Policies Impact on Development of Cocoa Farming in Indonesia - Emelda, Andi; Asrul , Laode; Mappigau, Palmarudi (Asian Journal of Agriculture and Rural Development, 2014)
Indonesian cocoa plantations from year to year increase, on the other hand decreased cocoa production andsome government policies have been carried out in order to increase exports and tried to occupy the first rank world cocoa exporting countries.This study aims to analyze (1) comparative and competitive advantages of cocoa farming in North Luwu, (2) the impact of government policies on development of cocoa farming in North Luwu.This is a descriptive analytic study. The sampling method used was purposive sampling of 40 farmers selected. Data collected through interviews, observation and documentation. Data were analyzed using the Policy Analysis Matrix (PAM).The results showed that the value of DRC and PCR of cocoa farming is respectively 0.03 and 0.04. The impact of government policies provide incentives to develop cocoa farming in North Luwu reflected NPCI value = 1.25; NPCO = 1.12, and EPC = 1.09 are all positive values.